PENETUAN BIOMASSA TEGAKAN (BATANG) MENGGUNAKAN PERSAMAAN ALOMETRIK DAN PERHITUNGAN NILAI EKONOMI KARBON TERSIMPAN PADA KAWASAN KPHP MODEL TASIK BESRA SERKAP BLOK E PROVINSI RIAU - Muhammad Abdul Hafiz; Aras Mulyadi; Tengku Nurhidayah (Program Pascasarjana Universitas Riau, 2019)
This study aims to analyze the vegetation of plants in Block E on the KPHP Model Tasik Besar Serkap by measuring the volume of trees, calculating the amount of stored biomass, calculating the amount of carbon and the economic value stored. The data in this study were obtained using the block method of conducting a field survey by making a Temporary Sample Plot (TSP) / Temporary Sample Plot and analyzed using plant vegetation analysis so that it can calculate the amount of carbon stored in the study area. KPHP Model Tasik Besar Serkap is one of the forest management units established based on the Decree of the Minister of Forestry No. 509 / Menhut-VII / 2010 covering two management areas namely Siak Regency and Pelalawan Regency with an area of 513,276 Ha. The details of limited production forests covering 2,660 hectares, permanent production forests covering 491,768 hectares and convertible production forests covering 18,848 hectares. Besides that, there is an area that has not been burdened with permits covering an area of 43,433 Ha which will be managed in that area. Among them is Block E covering 14,000 hectares. Research conducted, using the Alometric Model for Estimating Biomass and Carbon Stocks in the Block E in the KPHP Model Tasik Besar Serkap with reference to the Head of Forestry Research and Development Agency Regulation Number: P.01 / VIII-P3KR / 2012. The results of the study that have been carried out on 16 Record Units (RU) with a total RU total area of 1 Ha (10,000 m2), obtained stand biomass potential at Block E Research Site which is 1,354.38 tons / ha and Total stored carbon located in the Block E Research Site which is 621.84 tons / ha. With reference to the Ulu Masen carbon price, the economic value of carbon in Block E in the Tasik Besar Serkap KPHP area is US 34,823,040.00 or Rp.121,967,697,600.00, while the carbon value in Block E in the KPHP area of the Tasik Model The size of the Serkap per hectare is US 2,487.36 or Rp. 8,711,978.40,-.